2016
DOI: 10.1080/00224499.2015.1137539
|View full text |Cite
|
Sign up to set email alerts
|

“I Feel Like More of a Man”: A Mixed Methods Study of Masculinity, Sexual Performance, and Circumcision for HIV Prevention

Abstract: Ethnographic studies from numerous societies have documented the central role of male circumcision in conferring masculinity and preparing boys for adult male sexuality. Despite this link between masculinity, sexuality, and circumcision, there has been no research on these dynamics among men who have received a circumcision for HIV prevention. We employed a mixed methods approach with data collected from recently circumcised men in the Dominican Republic (DR) to explore this link. We analyzed survey data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
0
7
0
1
Order By: Relevance
“…Such influence through beliefs about sexual performance has also been reported in many studies in WHO priority SMC countries [30, 28, 21, 36, 29, 3739] and elsewhere [40]. Perception of partner preference for circumcised men has also been reported in other places [34, 24, 41, 26, 40, 42]. These widespread perceptions are also most likely influenced by the SMC social marketing campaigns.…”
Section: Discussionmentioning
confidence: 56%
“…Such influence through beliefs about sexual performance has also been reported in many studies in WHO priority SMC countries [30, 28, 21, 36, 29, 3739] and elsewhere [40]. Perception of partner preference for circumcised men has also been reported in other places [34, 24, 41, 26, 40, 42]. These widespread perceptions are also most likely influenced by the SMC social marketing campaigns.…”
Section: Discussionmentioning
confidence: 56%
“…Being unable or unwilling to perform sexually with a woman could make a man suspect of belonging to the ‘other’ type of sexualities (e.g. homosexual, asexual) that would preclude him from achieving the dominant ideal (67, 86, 87). This may encourage men in some settings to have a higher number of female sexual partners since research in various cultural contexts has shown that men who abstain from sex or refuse sex with a particular women are subject to teasing that challenges their masculine status (79, 81, 8890).…”
Section: Introductionmentioning
confidence: 99%
“…But some measures of sexual pleasure may increase after circumcision, as recently shown in sub-Saharan Africa and the Dominican Republic. The effect is likely because sexual pleasure is a multifaceted construct with biological, psychological, and cultural contributions (26, 27). These results suggest that adult men’s attitudes towards IMC are likely to be shaped by their beliefs about what circumcision does to sexual pleasure.…”
Section: Discussionmentioning
confidence: 99%